Are Transformation and Power Shifts All or Nothing Events? - Jacqlyn S. Triscari (Adult Education Research Conference, 2009)
This paper represents a qualitative case study conducted in one organization. It examines the role of power and shifts of power in an organization during an organizational transformation, a very specific form of change in which the center core or the worldview of the organization is altered.
Keywords: power; organizational transformation; change